Métis Kinscapes: Researching Métis Relations and Peoplehood at Lac Ste. Anne, AB ... - Gareau, Paul (University of Alberta Library, 2018)
SSHRC IDG Awarded 2018: The research seeks to disrupt settler, colonial, race-based understandings of the Métis-as-mixed and as victims of fragmented social geographies, by applying a place-based analysis of Métis peoplehood. Drawing on methods from Archaeology, History, Women's Studies, and more, this Aboriginal Research project will investigate kinscapes as the connective tissue of Métis relations both past and present, and examine the longstanding Catholic pilgrimage site of Lac Ste. Anne, AB as a not only a place of Catholic religious pilgrimage, but also a place for the maintenance and intensification of Métis kinscapes. ...